2010
DOI: 10.4061/2010/734182
|View full text |Cite
|
Sign up to set email alerts
|

Process Design and Economics of On-Site Cellulase Production on Various Carbon Sources in a Softwood-Based Ethanol Plant

Abstract: On-site cellulase enzyme fermentation in a softwood-to-ethanol process, based on SO2-catalysed steam pretreatment followed by simultaneous saccharification and fermentation, was investigated from a techno-economic aspect using Aspen Plus© and Aspen Icarus Process Evaluator© softwares. The effect of varying the carbon source of enzyme fermentation, at constant protein and mycelium yields, was monitored through the whole process. Enzyme production step decreased the overall ethanol yield (270 L/dry tonne of raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 34 publications
0
58
0
3
Order By: Relevance
“…The use of on-site enzyme production in 2G ethanol mills is a feasible way to reduce the costs associated with enzyme purification, addition of stabilizers and preservatives, transportation, and storage. This option should be considered in the design of 2G ethanol bioprocesses [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The use of on-site enzyme production in 2G ethanol mills is a feasible way to reduce the costs associated with enzyme purification, addition of stabilizers and preservatives, transportation, and storage. This option should be considered in the design of 2G ethanol bioprocesses [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid fraction of the slurry the yeast is cultivated and then supplemented with molasses. SSF is performed at 37 ºC with enzymes and yeast (Barta et al, 2010a;Sassner et al, 2008). The configuration of the process after SSF depends on the various combinations of the desired by-products.…”
Section: Biofuel Production Through Polygenerationmentioning
confidence: 99%
“…A techno-economic evaluation of the spruce-toethanol process, based on SO 2 -catalysed steam pretreatment followed by simultaneous saccharification and fermentation with various process configurations, achieved an ethanol cost of about 0.38-0.50 €/L. Anaerobic digestion of the stillage with biogas upgrading was a demonstrably favorable option in terms of both energy efficiency and ethanol production cost 8,9 and the contribution of enzyme is reported to be 0.04-0.05 €/L 9 . Ballerini et al 5 concluded that technical and economic optimization of the pretreatment step, the total substitution of lactose by pentose hydrolysate as the main carbon source for enzyme production, and the recycling of a fraction of the enzyme, the incorporation of pentose in ethanol fermentation, and the utilization of by-products all reduce the production cost of lignocellulosic ethanol.…”
Section: Cost Analysismentioning
confidence: 99%